Karhunen-Loéve decomposition of high Reynolds number turbulent pipe flows: A Voronoi analysis - Massaro, D.; Yao, J.; Rezaeiravesh, S.; Hussain, F.; Schlatter, P. (Journal of Physics: Conference Series, 2024)
We perform the Karhunen-Loéve decomposition of the data from direct numerical simulations pertaining to incompressible turbulent pipe flow at various Reynolds numbers, in order to identify large-scale coherent structures. A novel approach based on the Voronoi diagram is introduced to estimate the energy distribution along the radial direction as a function of the geometrical properties of the modes. In contrast to previous classifications, no user-defined criterion, threshold or ad-hoc separation of the eddies is required since the two most energetic branches are inherently present as the Reynolds number increases. Details about the Voronoi analysis are provided, together with a comprehensive validation and comparison with previous classifications at low Reynolds numbers. We discuss the results and potential of the presented approach at Reτ = 180 and 5200, commenting on the two classes of coherent structures with a varying and constant size in the radial direction appearing at Reτ = 5200.
CRIS-Team Scopus Importer:2024-05-24